DEVELOPMENT OF BUDGET RIGHT IN TURKEY - ERGEN, Eren (SSD Journal, 2022)
Budget can be expressed as the estimation of income and expenses for the next period. It is known that the income and expenses mentioned in ancient times were decided by the chieftain of that community. However, as a result of the arbitrary use of this authority, there has been an economic burden on the people. As a matter of fact, the people rebelled against the situation. Thus, the first steps were taken towards realizing the use of the public budget within the framework of certain principles. These developments were called budget rights and led to violent events in some periods. In other words, it is known that the acquisition of the budget right can be achieved as a result of bloody rebellions that took place in some periods. While this is the case in the West, in Turkey, it is possible to talk about the budget right offered to the public by the rulers rather than violent rebellions. The development of the budget right in Turkey dates back to the Ottoman Empire. However, in this period, it does not seem possible to talk about the right to budget in the modern sense. As a matter of fact, it is known that the right to the budget cannot be used effectively, and the audit of the budgetary applications cannot be made. In Turkey, it is seen that the right to budget in the modern sense was gained with the Republican period. In this study, it is aimed to focus on the development of the budget right in Turkey and how the 2017 Constitutional amendment affected the budget right. It is observed that some of the arrangements on the budget brought by the Presidential Government System may negatively affect the budget right.